Gambaran Klinis dan Histopatologi Karsinoma Urotelial di Salah Satu RS Swasta Jakarta Barat Tahun 2021-2023 - Andri Lesmana; Christina, Shintia; Indarto, Fanny; Boedijono, Freciyana (Jurnal MedScientiae, 2025)
Urothelial carcinoma is a type of cancer that can occur in organs lined with urothelial cells, specifically in the urinary tract. Globally, in 2022, bladder cancer accounted for 3% of all cancer cases. Objective to determine the clinical and histopathological characteristics of urothelial carcinoma patients at a private hospital in West Jakarta from 2021 to 2023. This study is a descriptive study with a retrospective approach conducted at a private hospital in West Jakarta. The sample size was determined using the consecutive sampling technique, resulting in a total of 40 samples. The highest number of urothelial carcinoma cases was recorded in 2021, with 21 cases (52.5%). In this study, 14 cases (35.0%) were found in the 60-69 age group. The most common clinical complaint was gross hematuria, observed in 34 samples (85.0%). Histopathological examination showed that the most frequent pathological stage was pT1, found in 14 samples (35.0%), while the most common pathological grading was high grade, observed in 29 samples (72.5%). The incidence of urothelial carcinoma at a private hospital in West Jakarta from 2021 to 2023 was 40 cases, with gross hematuria being the most common clinical complaint. The highest incidence was in the 60-69 age group. The most frequent pathological stage was pT1, and the most common pathological grading was high grade.